DBW 71: A new wheat variety for late sown irrigated conditions of north western plains zone of India - Singh, S K; Chatrath, R; Tiwari, V; Rao, NVPR Ganga; Kumar, Raj; Venkatesh, K; Mishra, C N; Tiwari, R; Singh, G; Tyagi, B S; Sharma, P; Kumar, Satish; et al. (Journal of Cereal Research, 2013)
A new high yielding bread wheat (Triticum aestivum) variety DBW 71 has been developed and released by Central Sub-Committee on crops standards and notifications and release of verity for agricultural crops for late sown cultivationunder and irrigated conditions of the North Western Plain Zone (NWPZ) of India during 2013. It has average yield of43.2 q ha-1 with yield potential of 68.9 q ha-1 and its plasticity for sowing period make it more suitable for cultivationafter basmati rice, sugarcane, cotton, vegetable peas, potato, etc. Higher yielding ability of DBW 71 under very latesown conditions reflects its better tolerance to terminal heat stress. The race specific APR response analysis and SRTagainst 78S84 pathotype of stripe rust showed high level of resistance in DBW 71 at adult plant and seedling stages.Besides, DBW 71 possesses better quality traits as indicated by higher protein content (13.4%), perfect Glu-1 score(10/10), better grain appearance (score 6.2) and hectoliter weight (78.4 kg hl-1).